BIBLIOMETRICS ANALYSIS AND MAPPING: THE TREND OF ‘ LEARNING METHOD” IN 2012-2022 - Elihami Elihami; Mohd. Melbourne (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This research explained the phases of the systematic process the Learning Method . This research is initiated with an article search through keyword of learning method in the Scopus database across 2012-2022 period which resulted 130 articles. Using descriptive analysis and processed-visualized data with the help of VOSviewer software, this study shows the three-dominant concepts that are mostly studied, they are learning method, learning, and method. This research contributes to show the development and urgency of learning method. Meanwhile, the limitation is that the articles reviewed were only sourced from Scopus. Therefore, this study suggests that future studies require the use of a comparative analysis approach by implementing the Web of Science (WoS) database and increases the duration of the latest article search period especially learning method.